Screening of the cytotoxic activity of Aquilaria malaccensis aqueous extract against selected cancer cell lines towards development of halal and toyyib anticancer agent - Eissa, Manar; Hashim, Yumi Zuhanis Has-Yun; Mohd Salleh, Hamzah; Abd Warif, Nor Malia (International Institute for Halal Research and Training (INHART), International Islamic University Malaysia (IIUM), 2021)
Aquilaria malaccensis produces a fragrant agarwood resin in response to injury. Several studies have reported different pharmacological effects of Aquilaria malaccensis leaves including anticancer activity. This study aims at screening the cytotoxic effects of the aqueous extract of Aquilaria malaccensis leaves using WST-1 cytotoxicity assay against six cancer cell lines, breast cancer cell line (MCF-7), lung cancer (A-549), cervical cancer cell line (HeLa), colorectal cell line (HT-29), liver cancer cells (HepG2), and prostate cancer (PC-3). The extract demonstrated cytotoxic effect against the MCF-7 and A549 cell lines with IC50 values equal to 74.72 and 95.62 µg/mL, respectively, while in the other cell lines the IC50 was above 100 µg/mL. The study suggests the possible use of the aqueous extract of A. malaccensis leaves as a Halal and Toyyib therapeutic anticancer agent.